Absolute CT perfusion parameter values after the neoadjuvant chemoradiotherapy of the squamous cell esophageal carcinoma correlate with the histopathologic tumor regression grade. Issue 12 (December 2015) - Djuric-Stefanovic, A.; Micev, M.; Stojanovic-Rundic, S.; Pesko, P.; Saranovic, Dj
Highlights: Neoadjuvant chemoradiation (nCRT) is standard therapy of esophageal carcinoma (EC). Accurate response evaluation of EC to nCRT became the main diagnostic challenge. Post-nCRT CT perfusion parameter values correlate with the histopathologic TRG. BF and BV were gradually rose and MTT decreased as TRG increased from 1 to 4. CT perfusion can improve accuracy in response evaluation of EC to nCRT. Abstract: Purpose: To analyze value of the computed tomography (CT) perfusion imaging in response evaluation of the esophageal carcinoma to neoadjuvant chemoradiotherapy (nCRT) using the histopathology as reference standard. Methods: Forty patients with the squamous cell esophageal carcinoma were re-evaluated after the nCRT by CT examination, which included low-dose CT perfusion study that was analyzed using the deconvolution-based CT perfusion software (Perfusion 3.0, GE). Histopathologic assessment of tumor regression grade (TRG) according to Mandard's criteria served as reference standard of response evaluation. Statistical analysis was performed using Spearman's rank correlation coefficient ( r S ) and Kruskal–Wallis's test. Results: The perfusion CT parameter values, measured after the nCRT in the segment of the esophagus that had been affected by neoplasm prior to therapy, significantly correlated with the TRG: blood flow (BF) ( r S = 0.851; p < 0.001), blood volume (BV) ( r S = 0.732; p < 0.001) and mean transit time (MTT) ( r S = −0.386; p = 0.014). Median values of BF and BV significantly differed among TRG 1–4 groups ( p < 0.001), while maximal esophageal wall thickness did not ( p = 0.102). Median BF and BV were gradually rose and MTT decreased as TRG increased, from 21.4 ml/min/100 g (BF), 1.6 ml/100 g (BV) and 8.6 s (MTT) in TRG 1 group, to 37.3 ml/min/100 g, 3.5 ml/100 g and 7.5 s in TRG 2 group, 81.4 ml/min/100 g, 4.1 ml/100 g and 3.8 s in TRG 3 group, and 121.1 ml/min/100 g, 4.9 ml/100 g and 3.7 s in TRG 4 group. In all 15 patients who achieved complete histopathologic regression (TRG 1), BF was <30.0 ml/min/100 g. Conclusions: CT perfusion could improve the accuracy in response evaluation of the esophageal carcinoma to nCRT.